EVALUATION OF UTERINE MICROCIRCULATION AS A KEY FACTOR IN THE PATHOGENESIS OF REPRODUCTIVE LOSS - Karimova F.D; Mutalova Z.L; Khodzhaeva A.S (Scholar Express Journal, 2025)
eproductive losses remain one of the most complex and multidisciplinary problems in modern obstetrics. Despite numerous established etiological factors, a key pathogenetic link is often the disruption of utero-placental blood flow, which is based on disorders at the microcirculatory level. Early diagnosis of these conditions is crucial for preventing pregnancy loss.
Keywords: Reproductive loss; Reproductive lossmicrocirculation